HORMONE STUDY IN FRESHWATER FISH CHANNA GACHUA (HAM-1822) DURING PRE-MATURE, MATURE AND SPAWNING BY ENZYME ASSAY BASED CHEMILUMINESCENCE TECHNOLOGY. - M.V.GAIKWAD; Y.K.KHILLARE (International Journal of Pharma and Bio Sciences, 2015)
The quantity of hormones were observed in premature fish C.gachua . A mature fish, with length (15cm) and weight (30 gm) Testosterone has been reported at 0.24 ng/ml in male and 0.04 ng/ml in female, Estradiol 0.004 pg/ml in male and 2.4 pg/ml in female. Progesterone (3.001 ng/ml) in female. DHEAS at 0.2 µg/ml in male and 0.2 µg/ml in female. Lutinizing hormone 0.2 mIU/ml in male and 0.6 mIU/ml in female. Follicle stimulating hormone, (FSH) 32.7 µg/ml in female. Thus, in spawning having length (15cm) and weight (35gm), quantity of testosterone 0.04 ng/ml in, Estradiol in female 0.4 pg/ml, Progesterone 2.01 ng/ml in female. DHEAS 0.002 µg/ml in male and 0.009 µg/ml in female) Lutinizing hormone in male 0.02 mIU/m0 and in female 0.2 IU/ml. Follicle stimulating hormone female 0.01 µg/ml., has been recorded significantly.